2020
DOI: 10.1007/s40866-020-00086-4
|View full text |Cite
|
Sign up to set email alerts
|

2M2C-R2ED: Multi-Metric Cooperative Clustering Based Routing for Energy Efficient Data Dissemination in Green-VANETs

Abstract: The aim of this paper is to focus on energy dissemination for green vehicle transportation. In current scenario population of urban areas keeps increasing as the people move towards the cities in search of jobs and betterlife style. This leads to an increase in the number of vehicles on the road. But the transport network which is accessible to the citizens is less when compared to their demand. This situation results in more vehicles on the road. The result of which is one of the factors that aggravate the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Chandramohan et al ( 2020 ) propose an efficient water dropping algorithm for VANET to find an alternative root for effective and pollution-less transportation. Xu Bao et al ( 2020 ) applied PSO-based clustering for routing V2V for improved optimized roots efficiency.…”
Section: Literature Studymentioning
confidence: 99%
“…Chandramohan et al ( 2020 ) propose an efficient water dropping algorithm for VANET to find an alternative root for effective and pollution-less transportation. Xu Bao et al ( 2020 ) applied PSO-based clustering for routing V2V for improved optimized roots efficiency.…”
Section: Literature Studymentioning
confidence: 99%
“…Clustering techniques are not only used in predicting road accident severity, but they can also be used in several other fields like management, arts, engineering, and medicine. 15 More recently, Sivasankaran and Balasubramanian 26 studied the patterns in road crashes in Tamil Nadu from 2009 to 2017 reported in the Road Accidents Database Management System (RADMS) to explore the injury severity levels of bicycle-vehicle crashes. Latent Class Clustering (LCC) models and binary logit models were combined to identify significant factors in demographics, vehicle, and environmental causes for the crashes.…”
Section: Related Workmentioning
confidence: 99%
“…They suggested that both K‐means and hierarchical clustering techniques are valuable tools in the arsenal of spatial analytic methods for road safety research. Clustering techniques are not only used in predicting road accident severity, but they can also be used in several other fields like management, arts, engineering, and medicine 15 …”
Section: Related Workmentioning
confidence: 99%
“…1) Influences of road congestion: Traffic congestion causes high fuel consumption and polluted gas emission. The design of vehicle routes can help to avoid obstacles and congestion on the road, release traffic congestion and reduce the overall energy consumptions [130]. M. R. Jabbarpour et al [131] propose an Ant-based Vehicle Congestion Avoidance System (AVCAS) to reduce fuel consumption and CO 2 emissions through the optimal path selection of a vehicle at each time interval.…”
Section: Green Vehicular Routingmentioning
confidence: 99%